Bioinspired Chitinous Material Solutions for Environmental Sustainability and Medicine. (1st July 2013) - Fernandez, Javier G.; Ingber, Donald E.
Abstract Chitin—the second most abundant organic material on earth—is a polysaccharide that combines with proteinaceous materials to form composites that provide the structural backbone of insect cuticles, crustacean exoskeletons, cephalopod shells and covering surfaces of many other living organisms. Although chitin and its related chitosan materials have been used in various industrial and medical applications based on their chemical properties, their unique mechanical functions have not date been leveraged for commercial applications. The use of chitinous materials for structural applications has been limited by our inability to reproduce, or even fully understand, the complex hierarchical designs behind naturally occurring chitin composites. In this article, an example of engineered chitinous materials is used to introduce the reader to the potential value that bioinspired materials offer for engineering of synthetic and biological materials. The nature of chitin and its general characteristics are first reviewed, and examples of chitinous structures are presented that are designed to perform very different functions, such as nacre and the insect cuticle. Investigation of the structural organization of these materials leads to understanding of the principles of natural materials design that are beginning to be harnessed to fabricate biologically‐inspired composites for materials engineering with tunable properties that mimic living materials, which might provide useful for environmental challenges, as well as medical applications.